Initial development of a measure to link psychotherapy-seeking adults with appropriate theoretically derived treatment - Neujahr, Nicholas E., author; Cesnales, Nicole I., advisor; Dakin, Emily K., committee member; Anderson, Sharon, committee member (Colorado State University. Libraries, 2014)
A multitude of differing theoretical approaches to psychotherapy exist in practice today. Many researchers have attempted to prove the superior effectiveness of one theoretical approach over another, yet most findings point to the overall equal effectiveness of psychotherapy across such theoretical approaches, a phenomenon known as the "do-do bird verdict." While some investigators continue to focus research efforts on therapists' approaches to treatment, more emphasis is being placed on clients' contribution to the therapeutic process. Despite this shift, little research exists that investigates clients' ability to relate to and incorporate any of the various models of treatment they may potentially encounter in treatment. The development of a measure intended to link psychotherapy-seeking adults with the appropriate theoretically based treatment is described, with an emphasis on clinical application. A panel of nine (n=9) clinical experts was recruited to review 117 items constructed to reflect six major theoretical approaches to psychotherapy. Inter-rater reliability and content validity were determined to determine the 48 strongest items. A cognitive interview was conducted to further determine clarity and understanding of these items, as well as to identify the five strongest items per domain to constitute the 30-item final measure. An outline for developing valid items that constitute the measure is provided, including recruitment and use of a panel of clinical experts to review and revise the instrument for content validity and clarity.